Evaluation of different tillage and intercropping systems in castor under rainfed conditions: Evaluation of different tillage and intercropping systems in castor under rainfed conditions - P VEERAMANI; V RAVICHANDIRAN; P A SARAVANAN; S MANICKAM; S R VENKATACHALAM; P ARUTCHENTHIL (Journal of Oilseeds Research, 2023)
The field experiments were conducted in 2020-21 and 2021-22 at Tapioca and Castor Research Station, Tamil Nadu Agricultural University, Yethapur. The pooled result of the two-year study of different tillage practices in castor based legume intercropping systems in rainfed, there was no significant difference among tillage practices relevant to growth, yield attributing characters, seed yield and biomass yield, numerically higher values were registered under conventional tillage practices over minimum tillage. The higher seed yield of both base (1152 kg/ha) and inter crop (481 kg/ha) were recorded in conventional tillage practices over minimum tillage. With respect to inter cropping, higher base crop (castor) yield of 1058 kg/ha was recorded under castor + groundnut inter cropping system which was observed to be on par with sole castor (1020 kg/ha) and castor + greengram (907 kg/ha). The highest. Moreover, the maximum benefit-cost ratio was recorded in castor + groundnut (1:3) intercropping, over sole castor cropping.